EFFECTS OF SMOKING ON CIRCADIAN ARTERIAL BLOOD PRESSURE PROFILE IN PATIENTS WITH NON-ST-SEGMENT ELEVATION ACUTE CORONARY SYNDROME AND CHRONIC KIDNEY DISEASE - Oksana Yadzhyn; Tetiana Solomenchuk (Acta Medica Leopoliensia)
The paper presents the results of a study of the effects of smoking on circadian arterial blood pressure (ABP) profile in patients with Non-ST-Segment Elevation Acute Coronary Syndrome (NSTE-ACS) and Chronic Kidney Disease (CKD).